Changing the Mindset to Encourage Innovation in Resolving Problems in the Built Environment: Exploring the Role of Online Gaming Platforms to Deliver Collaborative Learning and Teaching - Khan, Shahed; Brunner, Julie; Gibson, David (2018)
As educators we seek to set up meaningful graduate attributes to encourage creativity and a drive for innovation among our graduates in order to produce professionals not content with learning how to do more of the same, but who have the courage to push the boundaries of their profession and innovate. Referring to preparatory research on work in progress at Curtin University, we explored the capacity of team teaching using online gaming platform technology. We investigated the feasibility of engaging teams of students in practical applications of theoretical concepts of communicative and collaborative planning and decision-making, along with the dynamics and politics of community consultation in a pluralistic society. We ascertained the potential of developing students’ interpersonal and intercultural skills to develop collaborative partnerships through engagement with fellow students and a wide range of stakeholders/partners, simulating real-life situations using serious gaming platforms. It is contended that through a collaborative and experiential learning-approach to teaching and by employing state-of-the-art online gaming/teaching platforms, we could enable students to deal with real-life issues in simulated and sufficiently supervised conditions to encourage creativity and risk taking. This would encourage students to strive for creativity in solving contextual problems in their search for innovative solutions to complex and wicked problems. It is also contended that state-of-the-art delivery of curricula could free up academics during teaching sessions to concentrate on inspiring students to explore innovative and creative solutions for these problems.